Juridical Review the Effect of the Amendment of Law No. 13 of 2003 to Law No. 06 of 2023 On Termination of Employment (Layoff) - Muhammad Rizky Syamandiri; R. Rahaditya (Green Publisher Indonesia, 2025)
This study examines the juridical implications of amending Law No. 13 of 2003 to Law No. 6 of 2023 (Job Creation Law) on termination of employment in Indonesia. As a rechtsstaat country, Indonesia prioritizes the protection of constitutional rights, including workers' rights. However, the Job Creation Law has raised concerns regarding potential violations of workers' constitutional rights, particularly in termination of employment provisions. Using a normative juridical method with statutory, conceptual, and analytical approaches, this research analyzes problematic articles in the Job Creation Law that may contradict constitutional principles. The study finds that several provisions, including those on wages, working hours, employment contracts, and severance pay, have reduced workers' protections compared to the previous labor law. These changes potentially violate constitutional guarantees under Article 27(2) and Article 28D(2) of the 1945 Constitution. The research concludes that the Job Creation Law requires comprehensive evaluation and revision to ensure alignment with constitutional principles and adequate protection of workers' rights. This study contributes to the discourse on labor law reform and provides policy recommendations for strengthening constitutional protections in employment relations.